EXPERIMENTAL MODELING OF PLATINUM BEHAVIOR UNDER HYDROTHERMAL CONDITIONS (300-500°C AND 1 KBAR) - Plyusnina L.P.; Likhoidov G.G.; Shcheka Zh.A. (My University, 2007)
The behavior of Pt was studied in the Pt-Fe-S-Cl-H2O, Pt-Fe(Ni)-As-S-Cl-H2O, and Pt-Ni-As-Cl-H2O systems. Kinetic experiments showed that the addition of As and S to the system changes the character of Pt complexing and results in a decrease in the bulk Pt content in the solutions. The intermediate complexes that formed during this process disproportionated to produce cooperite and sperrylite. Under the experimental P-T-μ i conditions, the hydrothermal mobility of Pt was mainly provided by its hydrosulfide complexes with a definite participation of chloride complexes. The presence of Ni in the system lowers the redox potential and Pt solubility and prevents the formation of Pt phases, while Ni sulfides and arsenides crystallize copiously. The behavior of Pt and Au in hydrothermal systems and mechanisms of hydrothermal formation of noble metal minerals were considered.